2019
DOI: 10.1016/j.gde.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cytonemes in development

Abstract: Cell–cell communication is essential during the development of multicellular organisms. Specialized cell protrusions called cytonemes have been identified to exchange signals between cells that are vital for tissue development. Cytonemes can carry signalling components between distant cells and thus regulate the activity levels of the corresponding signalling pathways across entire tissues. This review summarizes the key findings on the formation and function of cytonemes in tissue development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…However, beyond the ECM layer of the basal side, the hemolymph current may disrupt any gradient of diffusive signals. Cytonemes, originally found in the fruit fly wing imaginal discs [75][76][77], have been detected on the basal side (but not the apical side) of the pupal wing epithelial cells in butterflies [45,46] and may play an important role in delivering signaling molecules to distant cells, resulting in a stable gradient of molecular morphogens. Nonmolecular (physical) morphogens, potentially in the form of a mechanical distortion signal of epithelial sheets, may require extracellular support materials to travel.…”
Section: Discussionmentioning
confidence: 99%
“…However, beyond the ECM layer of the basal side, the hemolymph current may disrupt any gradient of diffusive signals. Cytonemes, originally found in the fruit fly wing imaginal discs [75][76][77], have been detected on the basal side (but not the apical side) of the pupal wing epithelial cells in butterflies [45,46] and may play an important role in delivering signaling molecules to distant cells, resulting in a stable gradient of molecular morphogens. Nonmolecular (physical) morphogens, potentially in the form of a mechanical distortion signal of epithelial sheets, may require extracellular support materials to travel.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying assumption of simple diffusion of morphogens produced by source cells, which ultimately determines cell fate through the establishment of morphogen gradients, has been recently challenged due to the observation of other complex transport mechanisms [8]. Recently, a cytoneme-based transport mechanism has been linked to morphogen distribution [10]. Cytonemes are specialized filopodia that can, despite only delivering morphogens by short range directed transport, mediate long-distance signaling during development [9].…”
Section: Cytonemes As Transport Vehicle For Wnt Morphogensmentioning
confidence: 99%
“…Recent observations in other signaling systems, however, question the universality of both of these assumptions. Experiments in Drosophila and vertebrates suggest that distribution of morphogens through signaling filopodia—known as cytonemes—are a prerequisite to orchestrate patterning in quickly reorganizing developing tissue [ 8 10 ]. Recently, there is also evidence that cytonemes may play a further essential role in cancer progression [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a high cross-correlation amplitude indicates co-diffusion of bound Ror2-mCherry and Wnt8a-GFP and further experiments demonstrated that Wnt8a/Ror2 can activate the β-catenin-independent Wnt/PCP signalling pathway and thus promote filopodia formation (Mattes et al 2018 ). Based on the FCCS data, a further analysis showed that these filopodia are Wnt8a/Ror2-bearing protrusions—known as cytonemes—regulating extracellular Wnt dispersal (Zhang and Scholpp 2019 ; Mattes et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%